Hydrazone connected stable luminescent covalent–organic polymer for ultrafast detection of nitro-explosives. Issue 62 (9th December 2021) - Asad, Muhammad; Wang, Ya-Jie; Wang, Shan; Dong, Qing-Guo; Li, Lin-Ke; Majeed, Saadat; Wang, Qian-You; Zang, Shuang-Quan
Abstract : A novel H-COP was synthesized through Schiff-base condensation reaction, which shows high sensitivity ( K sv ∼ 10 6 M −1 ) and selectivity (μM level) towards nitro-explosives. Abstract : Developing promising luminescent probes for the selective sensing of nitro-explosives remains a challenging issue. Porous luminescent covalent–organic polymers are one of the excellent sensing probes for trace hazardous materials. Herein, fluorescent monomers 1, 1, 2, 2-tetrakis(4-formyl-(1, 1′-biphenyl))ethane (TFBE) and 1, 3, 5-benzenetricarboxylic acid trihydrazide (BTCH) were selected to build a novel hydrazone connected stable luminescent covalent–organic polymer (H-COP ) of high stability by typical Schiff-base reaction. The N2 sorption study, BET surface area analysis, and TGA profile indicate the porosity and stability of this H-COP material. Such properties of the H-COP material enable a unique sensing platform for nitro-explosives with great sensitivity ( K sv ∼ 10 6 M) and selectivity up to μM. This polymer material shows attractive selectivity and sensitivity towards phenolic nitro-explosives and other common explosives among earlier reported COP-based sensors.